Snapshots and Short Notes : Images and Messages of Early Twentieth-Century Photo Postcards - Wilson, Kenneth, 1944- (Book collections on Project MUSE., 2020)
"Book contains about 400 images of the fronts and backs of real photo postcards from about 1900-1920. These were postcards created by ordinary people from their own photographs and mailed with their messages on the back. Book also describes history of photography that resulted in people being able to create their own photos without a dark room, and explains known information about the specific cards, including who sent and received them and what they depict"--